Mid‐ to long‐term results of total ankle replacement in patients with haemophilic arthropathy: A 10‐year follow‐up. Issue 2 (22nd December 2017) - Eckers, F.; Bauer, D. E.; Hingsammer, A.; Sutter, R.; Brand, B.; Viehöfer, A.; Wirth, S. H.
Abstract : Introduction: Haemophilic ankle arthropathy is caused by recurrent spontaneous joint haemorrhaging and leads to pain, deformity and loss of function. In the presence of advanced articular deterioration, therapeutic options are confined to either arthroplasty or arthrodesis, the latter still being referred to as the procedure of choice. However, total ankle replacement (TAR) has recently gained acceptance as an alternative. Aim: To investigate the mid‐ to long‐term results of TAR in haemophilic ankle arthropathy. Materials and Methods: Seventeen TARs in 14 male patients (mean age: 43 years [range, 27.4‐57.6]), implanted between 1998 and 2012, were retrospectively analysed. Implant survival was estimated using Kaplan‐Meier analysis. Haemophilic/viral status, complications and revision surgeries were recorded. Follow‐up assessment of 12 TARs was performed 9.6 years (range, 3.3‐17.8) postoperatively, including clinical examination, pain and satisfaction scales, the American Orthopaedic Foot and Ankle Society (AOFAS) hindfoot score, and the SF‐36. Radiographic evaluation of pre‐ and follow‐up radiographs was conducted. Results: Estimated implant survival was 94% at 5, 85% at 10 and 70% at 15 years, respectively. Three cases required revision surgery. At follow‐up, 9.6 years (range, 3.3‐17.8) postoperatively, the level of satisfaction was 76% (range, 50‐100) and of pain 2/10 (range, 0‐6) on the VAS. Range of motion had increased significantly ( P = .037). The SF‐36 summary scores were comparable to those of a matched standard population. The AOFAS hindfoot score averaged 81 points (range, 73‐90). All radiographs revealed component loosening or periprosthetic radiolucency. Conclusion: Total ankle replacement in the presence of advanced haemophilic arthropathy is a viable treatment option with favourable mid‐/long‐term results, maintaining mobility of the ankle joint.